2021
DOI: 10.1192/bjo.2020.162
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the strength of exploratory suicide prediction models; from clinicians to computers

Abstract: Background Suicide prediction models have been formulated in a variety of ways and are heterogeneous in the strength of their predictions. Machine learning has been a proposed as a way of improving suicide predictions by incorporating more suicide risk factors. Aims To determine whether machine learning and the number of suicide risk factors included in suicide prediction models are associated with the strength of the resulting predictions. Method Random-effect meta-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 102 publications
1
18
0
Order By: Relevance
“…One review suggested, albeit with uncertainty, that the best performing machine learning methods in suicide prediction might bring performance equivalent to an odds ratio of 12, much less than what would be required under the second condition outlined above. [19] Across a range of epidemiological research areas, relative risks and likelihood ratios of the required magnitude are rarely observed and cannot be realistically expected. [20] While these relative measures may help in developing conceptual understanding of the general issues relating to low prevalence, we recommend that they be presented alongside absolute measures of risk when they are reported in particular studies.…”
Section: Discussionmentioning
confidence: 99%
“…One review suggested, albeit with uncertainty, that the best performing machine learning methods in suicide prediction might bring performance equivalent to an odds ratio of 12, much less than what would be required under the second condition outlined above. [19] Across a range of epidemiological research areas, relative risks and likelihood ratios of the required magnitude are rarely observed and cannot be realistically expected. [20] While these relative measures may help in developing conceptual understanding of the general issues relating to low prevalence, we recommend that they be presented alongside absolute measures of risk when they are reported in particular studies.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of NLP and ML was used in four studies [11][12][13][14]. ML as the exclusive AI technique was used in four studies [15][16][17][18], artificial neural network (ANN) was used in three studies [19][20][21], and NLP in two studies [9,22].…”
Section: Ai Toolsmentioning
confidence: 99%
“…A study by Corke et al (2021) mentioned that by increasing the number of suicide risk factors, ML can improve the performance of suicide risk prediction. However, its superiority over other methods has yet to be proven [17].…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 2 more Smart Citations